Relation of cultural and social attributes in dwelling, responding to privacy in Iranian Traditional House. - Mohamad Mahdi Shabani,; Mazlan Mohd Tahir,; Hoda Shabankareh,; Honey Arjmandi,; Fereshteh Mazaheri, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2011)
House as a shelter, from the early days of humanity, has been a worthy place, each culture and race has grown up under this shelter. Dwelling has always been such a fusion of living habits, environmental condition and cultural boundaries. Home is never created until there is a combination of comfort, fulfillment and a sense of belonging to a dwelling space. Privacy like security and peace is one of the rolling factors that affect housing forms. Since the past, Iranian architecture has emphasized on the relation between building and user. Culture and religious beliefs have concerned the Iranian user to have a suitable dwelling. The main result of this paper is that within Iranian traditional architecture the cultural affect on architecture has caused the division of the house in order to create privacy. These divisions by getting help from combination of open and closed spaces, has been formed professionally. The construction of the house was expanded in more than one floor with limited openings and view to outside; this is because of the inward looking feature of the traditional houses of Iran. On the other hand separation of house in to two or in some cases tree domains, public, private and in-between spaces has been one of these attempts, That made this architecture in accordance with people‟s culture and long lasting.